2015
DOI: 10.1038/srep13816
|View full text |Cite
|
Sign up to set email alerts
|

Multi-wavelength emission through self-induced second-order wave-mixing processes from a Nd3+ doped crystalline powder random laser

Abstract: Random lasers (RLs) based on neodymium ions (Nd3+) doped crystalline powders rely on multiple light scattering to sustain laser oscillation. Although Stokes and anti-Stokes Nd3+ RLs have been demonstrated, the optical gain obtained up to now was possibly not large enough to produce self-frequency conversion. Here we demonstrate self-frequency upconversion from Nd3+ doped YAl3(BO3)4 monocrystals excited at 806 nm, in resonance with the Nd3+ transition 4I9/2 → 4F5/2. Besides the observation of the RL emission at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 35 publications
1
32
0
1
Order By: Relevance
“…Even though the emitted RL spectrum is very narrow, as typical of rare-earth-doped RLs373839, it does not indicate single mode operation31. In fact, it has been recently shown that even for an ultranarrow smooth spectrum, as those emitted from random Raman lasers40, the emission is multimode, as reported in41.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Even though the emitted RL spectrum is very narrow, as typical of rare-earth-doped RLs373839, it does not indicate single mode operation31. In fact, it has been recently shown that even for an ultranarrow smooth spectrum, as those emitted from random Raman lasers40, the emission is multimode, as reported in41.…”
Section: Resultsmentioning
confidence: 97%
“…The RL system investigated in this work consisted of crystalline powders of Nd 3+ -doped YBO 3 (Nd:YBO) – Nd 3+ concentration: 4.0 mol%373839. The nanoparticle scatterers also act as the gain media.…”
Section: Resultsmentioning
confidence: 99%
“…Optical experiments were conducted in a similar scheme described in recent publications [14,25,26] where details are presented. The excitation source was the secondharmonic at 532 nm of a Nd-YAG laser operating at 5 Hz with beam area of 0.7 mm 2 , incidence angle of 30° with respect to the normal to the surface, and the excitation pulse energy (EPE) varied up to 4.60 mJ.…”
mentioning
confidence: 99%
“…The study of occupation sites is vital to understanding the photoluminescent features and the ion-ion interaction mechanisms that lead to photoluminescence quenching. Thereby, the synthesis with other lanthanide ions can be planned for used as nanothermometers, solar energy concentrators and laser devices [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%